Pain in Fabry Disease: Practical Recommendations for Diagnosis and Treatment. (28th March 2016) - Politei, Juan M.; Bouhassira, Didier; Germain, Dominique P.; Goizet, Cyril; Guerrero‐Sola, Antonio; Hilz, Max J.; Hutton, Elspeth J.; Karaa, Amel; Liguori, Rocco; Üçeyler, Nurcan; Zeltzer, Lonnie K.; Burlina, Alessandro
Summary: Aims: Patients with Fabry disease (FD) characteristically develop peripheral neuropathy at an early age, with pain being a crucial symptom of underlying pathology. However, the diagnosis of pain is challenging due to the heterogeneous and nonspecific symptoms. Practical guidance on the diagnosis and management of pain in FD is needed. Methods: In 2014, experts met to discuss recent advances on this topic and update clinical guidance. Results: Emerging disease‐specific tools, including FabryScan, Fabry‐specific Pediatric Health and Pain Questionnaire, and Würzburg Fabry Pain Questionnaire, and more general tools like the Total Symptom Score can aid diagnosis, characterization, and monitoring of pain in patients with FD. These tools can be complemented by more objective and quantifiable sensory testing. In male and female patients of any age, pain related to FD can be an early indication to start disease‐specific enzyme replacement therapy before potentially irreversible organ damage to the kidneys, heart, or brain occurs. Conclusion: To improve treatment outcomes, pain should be diagnosed early in unrecognized or newly identified FD patients. Treatment should include: (a) enzyme replacement therapy controlling the progression of underlying pathology; (b) adjunctive, symptomatic pain management with analgesics for chronic neuropathic and acute nociceptive, and inflammatory or mixed pain; and (c) lifestyle modifications.